DIGITAL LITERATION THROUGH ONLINE MAGAZINE IN LEARNING READING COMPREHENSION IN ELEMENTARY SCHOOL - Ruli Setiyadi; Uus Kuswendi; Muhammad Ghiyats Ristiana (IKIP Siliwangi, 2019)
The research aims to develop students' reading comprehension skills through the use of online magazines. The choice of online magazines as a source of student reading is because now students prefer to use electronic devices such as cellphones or laptops. The use of online magazines in primary school students can be an effort to instill digital literacy. This study uses a pre-experimental method with Post-test only with Nonequivalent Groups. The study population was grade IV students in the city of Cimahi while the selected sample of 28 students used the convenience technique. Meanwhile, the data collection technique uses a reading comprehension skills test and a digital literacy level questionnaire. Researchers conducted data analysis with inference statistics through the SPSS 20.0 program. The results indicated that the reading skills of group A students' understanding were better than those of group B. The researchers concluded that the online magazine had an effect on reading comprehension skills of grade IV students.